Darstellung und Charakterisierung der vier isomeren [2.2](2,5)Pyridinophane - J. Bruhin; W. Jenny (CHIMIA)
The Hofmann-l,6-elimination reaction of 2-methyl-picolinyl(5)-trimethylammonium hydroxide led to a mixture of isomeric [2.2](2,5)pyridinophanes in good yield. All four possible isomeres are separated by gas chromatography in pure state. The 1H-NMR spectra of [2.2](2,5)pyridinophanes show pseudo-geminal and pseudo-ortho downfield shifts.